STUDI ETNOGRAFI DESAIN: PERKEMBANGAN RAGAM HIAS MOTIF BATIK DESA WISATA KETAPANRAME KABUPATEN MOJOKERTO JAWA TIMUR - Ninik Juniati; Veny Megawati; Hari Hananto; Njoto Benarkah (PANGGUNG, 2026)
This study investigates how design ethnography can be used to develop batik motifs as a visual identity for a tourism village. The research was conducted in Ketapanrame village, East Java, using a qualitative ethnographic approach combined with design thinking. Data were collected through participatory observation, in-depth interviews, and documentation across five iterative development cycles from 2019 to 2022, with follow-up observations until 2025. The study demonstrates how ethnographic insights into daily practices, coffee culture, village landscapes, and clothing habits were systematically translated into visual design through mood boards, prototyping, product-use evaluation, reflection, and iterative adaptation. The findings reveal that batik motifs function not only as visual products but also as cultural artifacts embedded in social practices, as reflected in their adoption in village uniforms, udeng, sarongs, home décor, and tableware. This study contributes by proposing a model of artwork creation that translates ethnographic data into design outcomes through an iterative design thinking process, highlighting how visual identity is formed through social adoption rather than purely aesthetic considerations.